KIDNEY AND URINARY TRACT AND THEIR DISEASES - Fatima Sharipovna Nazarova; Sevinch Salimovna Abdurakhimova (Western European Studies, 2024)
The main function of the kidneys is to separate metabolic products of salt dissolved in urine . In addition, the kidneys produce biologically active substances that participate in the regulation of hemodynamics in the processes of protein, carbohydrate and fat metabolism. All the blood in our body flows through the kidneys every 5-10 minutes . Urine separation is called diuresis - emptying the bladder when it is full. This is a complex physiological process that occurs due to the contraction of the bladder muscle and the relaxation of the sphincter. When the bladder is full, the mechanoreceptors convey the impression of nerve impulses to the central nervous system, and the process is carried out. A person can secrete 1.5-2 liters of urine in one day . When sweating a lot in the high temperature of the environment, the amount of urine can decrease as a result of water leaving with sweat. After a meal, water and food salts are pushed into the intestine, increasing the production of urine. The color of urine varies from pale yellow to reddish-yellow depending on pigments. The appearance of urine color and protein in urine is a sign of pathology. is considered
Keywords: Nephrology; protein; diuresis; polyuria